Standardization of Pancaguna Taila - Saxena, R.B. (Asian Journal of Chemistry, 2010)
The title investigation is in continuation of our earlier works on the standardisation of pancaguna taila used in panchakarma therapy. The physical constants of tila taila, murchhita tila taila, eucalyptus taila, turpentine taila, kejoputi taila and pancaguna taila have been determined, the effect of packing and adulteration have also been studied.